Acute effects of different warm-up duration on internal load and external load responses of soccer players in small sided games - Yilmaz, O.; Ozturk, F.; Batalik, L. (BMC Sports Science, Medicine and Rehabilitation, 2025)
Background Soccer is a dynamic sport that involves high-intensity running, changes of direction, jumping and contact. Therefore, a proper warm-up duration is of great importance to optimize players'performance and minimize the risk of injury.